Multi-rate co-simulation of power system transients using dynamic phasor and EMT solvers - Rupasinghe, Janesh; Filizadeh, Shaahin; Gole, Aniruddha M; Strunz, Kai (Journal of engineering (Stevenage, England), 2020)
This study presents a novel multi-rate algorithm for the co-simulation of power system transients using base-frequency dynamic phasor solver for frequency adaptive simulation of transient (BFAST) and electromagnetic transient (EMT) solvers. The BFAST solver alters its solution technique from dynamic phasors to EMT based upon the frequency contents of the waveforms being simulated. A changeover algorithm between the two solvers is also presented. The BFAST solver is then integrated with an industrial-grade EMT solver to develop a BFAST–EMT multi-rate co-simulator. The interface between the two solvers is established using transmission lines at the partitioning locations. The co-simulator combines the benefits of dynamic phasors, frequency adaptive simulation of transients, parallel processing, and multi-rate simulation. The study describes the several solution modes of the proposed co-simulator. Illustrative examples are included to demonstrate the accuracy and computational benefits of the proposed co-simulator.